Effects of Soil Water Deficit on Insecticidal Protein Expression in Boll Shells of Transgenic Bt Cotton and the Mechanism - Zhang, Xiang; Wang, Jian; Peng, Sheng; Li, Yuan; Tian, Xiaofeng; Wang, Guangcheng; Zhang, Zhongning; Dong, Zhaodi; Chen, Yuan; Chen, Dehua (Frontiers in Plant Science, 2017)
This study was conducted to investigate the effects of soil water deficit on insecticidal protein expression in boll shells of cotton transgenic for a Bt gene. In 2014, Bt cotton cultivars Sikang 1 (a conventional cultivar) and Sikang 3 (a hybrid cultivar) were planted in pots and five soil water content treatments were imposed at peak boll stage: 15% (G1), 35% (G2), 40% (G3), 60% (G4) and 75% field capacity (CK) respectively. Four treatments (G2, G3, G4, and CK) were repeated in 2015 in the field. Results showed that the insecticidal protein content of boll shells decreased with increasing water deficit. Compared with CK, boll shell insecticidal protein content decreased significantly when soil water content was below 60% of maximum water holding capacity for Sikang 1 and Sikang 3. However, increased Bt gene expression was observed when boll shell insecticidal protein content was significantly reduced. Activity assays of key enzymes in nitrogen metabolism showed that boll shell protease and peptidase increased but nitrogen reductase and glutamic-pyruvic transaminase (GPT) decreased. Insecticidal protein content exhibited significant positive correlation with nitrogen reductase and GPT activities; and significant negative correlation with protease and peptidase activities. These findings suggest that the decrease of insecticidal protein content associated with increasing water deficit was a net result of decreased synthesis and increased decomposition.